ANP32E induces tumorigenesis of triple‐negative breast cancer cells by upregulating E2F1. Issue 6 (18th April 2018) - Xiong, Zhenchong; Ye, Liping; Zhenyu, He; Li, Fengyan; Xiong, Yahui; Lin, Chuyong; Wu, Xianqiu; Deng, Guangzheng; Shi, Wei; Song, Libing; Yuan, Zhongyu; Wang, Xi
Abstract : Triple‐negative breast cancer (TNBC) lacks expression of estrogen receptor (ER), progesterone receptor, and the HER2 receptor; it is highly proliferative and becomes the deadliest forms of breast cancer. Effective prognostic methods and therapeutic targets for TNBC are required to improve patient outcomes. Here, we report that acidic nuclear phosphoprotein 32 family member E (ANP32E), which promotes cell proliferation in mammalian development, is highly expressed in TNBC cells compared to other types of breast cancer. High expression of ANP32E correlates significantly with worse overall survival (OS; P < 0.001) and higher risks of disease recurrence ( P < 0.001) in patients with TNBC. Univariate and multivariate Cox‐regression models show that ANP32E is an independent prognostic factor in TNBC. Furthermore, we discovered that ANP32E promotes tumor proliferation in vitro by inducing G1/S transition, and ANP32E inhibition suppresses tumor formation in vivo . By examining the expression of E2F1, cyclin E1, and cyclin E2, we discovered that ANP32E promotes the G1/S transition by transcriptionally inducing E2F1. Taken together, our study shows that ANP32E is an efficient prognostic marker, and it promotes the G1/S transition and induces tumorigenesis of TNBC cells by transcriptionally inducing E2F1. Abstract : Acidic nuclear phosphoprotein 32 family member E (ANP32E) is a negative prognostic factor that enhances tumorigenesis and cancer proliferation by promoting the G1/S transition in triple‐negative breast cancer (TNBC). ANP32E promotes the G1/S progression by upregulating E2F1 expression. TNBC patients with high expression of ANP32E might have a higher risk of disease recurrence, and they may consider undergoing more aggressive treatments and frequent disease surveillance.